2015
DOI: 10.1007/s12194-015-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

Iterative image reconstruction that includes a total variation regularization for radial MRI

Abstract: This paper presents an iterative image reconstruction method for radial encodings in MRI based on a total variation (TV) regularization. The algebraic reconstruction method combined with total variation regularization (ART_TV) is implemented with a regularization parameter specifying the weight of the TV term in the optimization process. We used numerical simulations of a Shepp-Logan phantom, as well as experimental imaging of a phantom that included a rectangular-wave chart, to evaluate the performance of ART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…16,17 ) validated direct estimation methods for higher undersampling rate of 100× and gave the flexibility to incorporate any prior. Experiments with the breast data 13 showed that at low undersampling rates, DLbased indirect methods perform significantly better; however, at higher undersampling rate, the iterative direct techniques using total variation (TV) 19 regularization perform significantly better. However, direct iterative techniques are computationally expensive and require manual tuning of hyper parameters.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 ) validated direct estimation methods for higher undersampling rate of 100× and gave the flexibility to incorporate any prior. Experiments with the breast data 13 showed that at low undersampling rates, DLbased indirect methods perform significantly better; however, at higher undersampling rate, the iterative direct techniques using total variation (TV) 19 regularization perform significantly better. However, direct iterative techniques are computationally expensive and require manual tuning of hyper parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, an iterative CT reconstruction algorithm with Edge-Preserving TV (EPTV) regularization was developed to reconstruct CT images from highly under-sampled data obtained with few-view and limited-angle data [23,[30][31]. In the unfully-collected k-space Magnetic Resonance Image (MRI) with non-uniform random sampling, a variation-based reconstruction approach was used for resolution enhancement of volumetric images, with the purpose to preserve important edges containing anatomical information [32]. Moreover, the randomness of the detected photons in positron emission tomography (PET) requires TV regularization to suppress noise while maintaining sharp edges without oscillations [33].…”
Section: Introductionmentioning
confidence: 99%